2014
DOI: 10.3329/jom.v15i1.19856
|View full text |Cite
|
Sign up to set email alerts
|

Dengue NS1 Antigen: A Tool in Early Detection of Dengue Virus Infection

Abstract: Objectives: This aim of the study was to evaluate the efficacy of NS1 antigen assay for early diagnosis of dengue virus infection in a tertiary care hospital. Methods: This cross sectional study was carried out in medicine unit of Square hospital from May to August 2013. Total 100 patients with dengue fever were included. Complete blood count, alanine aminotransferase (ALT), aspartate aminotransferase (AST), Dengue NS1 antigen and IgM and IgG antibodies of dengue virus were done in all cases. Results: Of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Dengue fever (DF) is an arthropod-borne viral disease that affects over 100 million cases worldwide [1,2]. Bangladesh is a country that is most adversely affected by dengue almost every year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue fever (DF) is an arthropod-borne viral disease that affects over 100 million cases worldwide [1,2]. Bangladesh is a country that is most adversely affected by dengue almost every year [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the male percentage (70%) was higher than the female percentage (30%) (Fig: 2). Similarly, the male ratio was higher in Barisal but inhabitant frequency is unknown to us in the case of Dhaka dengue outbreak (25,26). Global studies also showed male ratio is higher than females.…”
Section: Resultsmentioning
confidence: 90%